Business Models for Sustainability: Energy Efficiency in Urban Districts. (March 2016) - Gauthier, Caroline; Gilomen, Bettina
The disruptive nature of many sustainability solutions may be the main barrier to their implementation and dispersal: adopting a business model perspective may help address this problem. Previous literature has explored how organizations can convert their supply chains and customer interfaces toward a sustainability focus, but has generally not considered links to other business model elements—such as value propositions and financial models—in exploring business model transitions. Moreover, the implementation of sustainable solutions often relies on projects being implemented and managed collectively, so that organizations need to adapt their business models to deliver value propositions collectively, a phenomenon that research on business models for sustainability should address. This article addresses these issues by exploring changes in business model elements in detail via an in-depth qualitative study of two French sustainable urban projects— Caserne de Bonne and IssyGrid ®. Our results show, first, that it is worth considering the role played by business model elements (the value proposition and the financial model) that literature does not usually discuss in enabling the management of or transition to business models for sustainability. Second, considering all four business model elements allows us to develop a typology of their transformations in organizations working toward sustainable solutions. Third, introducing the necessary collective dimension of sustainable solutions highlights the role of agency in facilitating their development and adoption.